Takotsubo or Stress Cardiomyopathy - Bounhoure, J. P. (Hindawi Publishing Corporation, 2012)
Many case reports have been published of reversible left ventricular dysfunction precipitated by sudden emotional stress. We have evaluated 10 women hospitalized for acute chest pain and dyspnea, mimicking an acute coronary syndrome, after a severe emotional trigger. Those patients, postmenopausal women, presented ST segment alterations on the EKG, minor elevations of cardiac enzymes, and biomarkers levels. At the coronarography there was not coronary thrombosis or severe stenosis, but the ventriculography showed wall motion abnormalities involving the left ventricular apex and midventricle, in the absence of significant obstructive coronary disease. The course was benign without complication, with a full recovery of left ventricular function in some weeks. These observations, like other reports, demonstrate the impact of emotional stress on left ventricular function and the risk of cardiovascular disease. The cause of this cardiomyopathy is still unknown, and several mechanisms have been proposed: catecholamine myocardial damage, microvascular spasm, or neural mediated myocardial stunning.